Loss of Elp1 in cerebellar granule cell progenitors models ataxia phenotype of Familial Dysautonomia - Arnskötter, Carl Frederik; da Silva, Patricia Benites Goncalves; Schouw, Mackenna E.; Lukasch, Chiara; Bianchini, Luca; Sieber, Laura; Garcia-Lopez, Jesus; Ahmad, Shiekh Tanveer; Li, Yiran; Lin, Hong; Joshi, Piyush; Spänig, Lisa; et al. (Neurobiology of disease, 2024)
Familial Dysautonomia (FD) is an autosomal recessive disorder caused by a splice site mutation in the gene ELP1, which disproportionally affects neurons. While classically characterized by deficits in sensory and autonomic neurons, neuronal defects in the central nervous system have also been described. Although ELP1 expression remains high in the normal developing and adult cerebellum, its role in cerebellar development is unknown. To explore the role of Elp1 in the cerebellum, we knocked out Elp1 in cerebellar granule cell progenitors (GCPs) and examined the outcome on animal behavior and cellular composition. We found that GCP-specific conditional knockout of Elp1 (Elp1cKO) resulted in ataxia by 8 weeks of age. Cellular characterization showed that the animals had smaller cerebella with fewer granule cells. This defect was already apparent as early as 7 days after birth, when Elp1cKO animals also had fewer mitotic GCPs and shorter Purkinje dendrites. Through molecular characterization, we found that loss of Elp1 was associated with an increase in apoptotic cell death and cell stress pathways in GCPs. Our study demonstrates the importance of ELP1 in the developing cerebellum, and suggests that loss of Elp1 in the GC lineage may also play a role in the progressive ataxia phenotypes of FD patients.